Strength and conditioning considerations for female tackle football players - Brown, B. W.; Lopez, R. M. (Strength and Conditioning Journal, 2016)
Women's professional tackle football (11 versus 11) often consists of a wide range of athletes with various backgrounds and experiences. These challenges and the lack of awareness of this sport have resulted in a paucity of research and clinical data. The purpose of this review is to provide recommendations for strength and conditioning of female american football players based on the existing literature and to provide an example of an existing strength and conditioning program for women's tackle football. Future research should focus on the use of strength and conditioning for improving performance and preventing injury in this athlete population.